A description of Ternate Malay - Litamahuputty, Betty (UI Scholars Hub, 2012)
Ternate Malay is a local variety of Malay in Ternate, a small island in the Maluku Utara province in eastern Indonesia. The majority of speakers live in Ternate town, where it serves as mother tongue as well as a means of communication between people of various ethnic and linguistic backgrounds. In the last few decades there is a growing scholarly interest in local Malay varieties, particularly in the eastern part of Indonesia. This article is a short description of Ternate Malay based on the idea that words in Ternate Malay receive their meaning in the combination with other words and that the linguistic context as well as the non-linguistic situation in which they occur, determine the most suitable interpretation of utterances. It is shown how certain words facilitate the determination of the interpretation.